2002
DOI: 10.1093/cercor/12.10.1016
|View full text |Cite
|
Sign up to set email alerts
|

Oculomotor Effects of delta-9-Tetrahydrocannabinol in Humans: Implications for the Functional Neuroanatomy of the Brain Cannabinoid System

Abstract: The significance of cannabinoid signaling for human cognition and motor control is still poorly understood. Here, we have investigated acute behavioral effects of oral delta-9-tetrahydrocannabinol (THC) with oculomotor paradigms in 12 healthy human subjects. Compared to baseline testing: (i) THC increased latencies of reflexive visually guided saccades, while their accuracy was not affected; (ii) latencies of memory-guided saccades were unaffected, but THC modulated accuracy of these eye movements by increasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
33
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 56 publications
10
33
1
Order By: Relevance
“…This finding is in line with a previous study that reported more frequent reinspections of previously fixated areas in a visual search task (Huestegge et al 2002), and with the finding that in basic oculomotor tasks, chronic cannabis users had altered saccade amplitudes when they were asked to saccade to memorized screen positions (Huestegge et al 2009a). In sum, these deficits point to a deficit in working memory performance, which is also one of the most consistently replicated deficits in studies of acute cannabis effects (e.g., see Fletcher et al 1996;Lamers et al 2006;Ploner et al 2002;Rodgers 2000;Solowij and Battisti 2008;Solowij et al 2002).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This finding is in line with a previous study that reported more frequent reinspections of previously fixated areas in a visual search task (Huestegge et al 2002), and with the finding that in basic oculomotor tasks, chronic cannabis users had altered saccade amplitudes when they were asked to saccade to memorized screen positions (Huestegge et al 2009a). In sum, these deficits point to a deficit in working memory performance, which is also one of the most consistently replicated deficits in studies of acute cannabis effects (e.g., see Fletcher et al 1996;Lamers et al 2006;Ploner et al 2002;Rodgers 2000;Solowij and Battisti 2008;Solowij et al 2002).…”
Section: Discussionsupporting
confidence: 89%
“…Previous research on the effects of cannabis on eye movement control revealed both acute and long-term effects. For example, acute effects of cannabis were studied in a pre-post design involving the execution of basic visually and memory-guided eye movements in non-regular users (Ploner et al 2002). As one key result, saccade latencies of visually guided saccades were increased (12 ms), and amplitudes of memory-guided saccades were greater 2 h after oral drug intake compared to baseline testing.…”
Section: Introductionmentioning
confidence: 99%
“…It is perhaps interesting to note that somewhat parallel results were recently obtained in studies on Cannabis intoxication by Ploner et al (2002). They found increased amplitudes for memory-guided saccades under THC intoxication.…”
Section: Discussionsupporting
confidence: 76%
“…For instance, cannabis has been found to increase errors on both an antisaccade and a memory-guided saccade task (Ploner et al, 2002). Further, countermanding tasks have been used to measure effects of anesthetics on attentional inhibition.…”
Section: Examination Of Acute Drug Effectsmentioning
confidence: 99%